A system literature review on evolution of big data analytics application - Adrian, Cecilia; Sidi, Fatimah; Affendey, Lilly Suriani; Ishak, Iskandar (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper presents a systematic review on evolution of Big Data Analytics application. The review goal is to identify the evolution from traditional data analytics to big data analytics, and finding out the Big Data Analytics application research were conducted.